Penentuan Kadar Flavonoid dan Aktivitas Anti-Inflamasi Ekstrak Dan Fraksi Daun Sungkai (Peronema canescens Jack) - Aulena, Desi Nadya; Yani, Dwi Fitri; Mariyamah, Mariyamah; Tondi, Muhammad Lufika; Dandi, Muhammad; Wahyudin, Hafis Kiki; Raihan, Dany (Faculty of Pharmacy, Universitas Pancasila, 2023)
The SARS-CoV-2 virus is the infectious agent that causes COVID-19, a feverish condition brought on by inflammation in the infected patient’s body. Sungkai leaf (Peronema canescens Jack) is one of the Indonesian people who rely on herbal remedies to treat COVID-19. This study aims to determine how much flavonoids are present in ethanol, ethyl acetate, and n-hexane extracts, as well as the anti-inflammatory properties of ethanol extract, ethanol fraction, and n-hexane fraction of Sungkai leaves. The procedure was performed in-vitro with a UV-Visible spectrophotometer by observing the absorption response to inhibition of denaturation of inflammatory protein. The inhibition value was then computed via linear regression, and the IC50 and IC70 values were ascertained afterward. The ethanol fraction, ethanol extract, and n-hexane fraction in this investigation had the best inhibition values (%) at a concentration of 15 ppm, corresponding to 74.27%, 54.48%, and 18.52%. The sungkai leaves ethanol fraction > n-hexane fraction > ethanol extract had the best IC50 and IC70 values. Comparatively, the ethanol extract contained the largest amounts of flavonoids, 38.782 μg/mL.